STUDENTS’ PERCEPTION TOWARDS THE USE OF MULTIMEDIA BASED TEACHING MATERIAL - Leora Grahadila Andovita; Asih Wahyuni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The development of media in a conception of learning technology must have the following characteristics: (a) target oriented; (b) applying the concept of a systems approach; and (c) make use of varied learning resources. Thus the application of media and educational technology, can realize a concept of "teaching less learning more". As technology-based media variations develop, teaching materials become more interesting. Not only text and images, but there is audio, video and animation that make a concept easier to understand. Presentation of information in several ways and forms is often called multimedia. This research method is a survey research that aims to obtain information on students' perceptions of the use of PowToon multimedia-based teaching materials. The questionnaire was used as an instrument to obtain this information. The results of the questionnaire were then analyzed using the Technology Acceptance Model (TAM) model approach; namely: perceived usefulness (perceived usefulness), perceived ease of use, attitude toward using technology, and behavioral intention to use